Elastics in orthodontics: a review - Singh, VP; Pokharel, PR; Pariekh, K; Roy, DK; Singla, A; Biswas, KP (Health Renaissance, 2012)
For some decades elastics have been a valuable adjunct of any orthodontic treatment .Synthetic elastomers overcome various limitations of natural rubber. The use of elastics in clinical practice is predicted on force extension values given by the manufacturer for different sizes of elastics. Elastics can be used in various configurations for correction of a particular malocclusion. To minimize the plaque retaining capacity of elastomeric chains and risk of demineralization fluorides releasing elastomeric ligatures have been introduced. The elastics however don’t apply a continuous force over a interval of time due to the force degradation and are therefore inferior to Niti springs. There are increased incidences of latex allergies being reported in the literature and non latex products are available to overcome this limitation. It is very important for the orthodontist to educate the patient regarding the correct use of elastics as treatment results are dependent on patient cooperation. This article strives to summarize the currently available data on the various aspects of elastics including their properties, clinical usage and limitations. DOI: http://dx.doi.org/10.3126/hren.v10i1.6008 HREN 2012; 10(1): 49-56